2003
DOI: 10.1046/j.1365-2982.2003.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic motor activity in slow‐transit idiopathic constipation as identified by 24‐h pancolonic ambulatory manometry

Abstract: Colorectal motor activity in slow-transit idiopathic constipation has not been fully evaluated under physiological conditions. The aim of this study was to evaluate colorectal motor activity in chronic idiopathic constipation using 24-h ambulant pancolonic manometry. Ten healthy volunteers (six females) 19-31 years of age, and eight females 25-46 years of age with slow-transit idiopathic constipation were studied. Motor activity was measured using two custom-made silicone-coated catheters, each with five solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
4
49
1
1
Order By: Relevance
“…They are presumed to underlie the propulsion of colonic content, but this has not been demonstrated. It is important to note that a previous study of human colon found CMCs also occurred less frequently (9). Whether the CMCs we recorded in vitro are the same phenomena as the CMCs recorded in vivo is not known.…”
Section: Differences In Cmc Pacemaker Frequencies In Colons From Stc mentioning
confidence: 61%
See 2 more Smart Citations
“…They are presumed to underlie the propulsion of colonic content, but this has not been demonstrated. It is important to note that a previous study of human colon found CMCs also occurred less frequently (9). Whether the CMCs we recorded in vitro are the same phenomena as the CMCs recorded in vivo is not known.…”
Section: Differences In Cmc Pacemaker Frequencies In Colons From Stc mentioning
confidence: 61%
“…classification of CMCs described in dog colon (22) and human colon (9,23). CMCs in both dog and human colon in vivo occur repetitively and cyclically and can originate at any site along the colon, while being able to propagate in either an oral or anal direction.…”
Section: Terminology and Classification Of Colonic Motor Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…G proteins; cyclooxygenase enzymes; prostaglandins IDIOPATHIC CONSTIPATION is prevalent in young women and is characterized by slow transit time (3,16,41). Female sex hormones have been suggested as possible etiologic factors in the pathogenesis of slow-transit constipation (STC) because of the higher incidence of constipation in young women than in men (29,35) as well as during the last two trimesters of pregnancy, when the levels of progesterone (P 4 ) are highest (2,5,11,13,26,28,42).…”
mentioning
confidence: 99%
“…These typically have amplitude \50 mmHg [156], occur 40-120 times in a 24 h period [117,147,157], and propagate for distances \22.5 cm [121]. Studying the relation between frequency of PSs and constipation, some authors have found a reduced frequency in obstructed defecation [122] and slow transit constipation [155]; others have found no difference [151]. In healthy individuals, propagating sequences display a spatio-temporal or ''regional linkage'' (where two consecutive PSs, originating from different colonic regions overlap) [120,158].…”
Section: Colonic Motor Activitymentioning
confidence: 99%